Angioedema due to enalapril. A case report - Belkis Barrios Romero; Ana María Ramos Cedeño; Yeny Dueñas Pérez; Mirtha Amarilis Hernández López (Medisur)
Angiotensin converting enzyme inhibitors are used by more than 40 million people worldwide for the treatment of cardiovascular diseases. They are considered safe, although they can cause severe angioedema in 0.1 to 0.5% of patients. The case of a 67-years-old male patient diagnosed with diabetes mellitus and arterial hypertension, treated with metformin, hydrochlorothiazide and enalapril for approximately four years, who was admitted to the emergency room with severe edema of the third anterior of the tongue, without respiratory compromise is presented. Hydrocortisone and diphenhydramine were indicated and he evolved satisfactorily, for which he was discharged and prednisone and diphenhydramine were prescribed orally; he discontinued enlapril, 48 hours later he was reassessed and was asymptomatic. The mechanism by which these drugs produce angioedema is not clear, but it would probably be due to the tissue accumulation of bradykinin and can occur at any time during treatment. The correct history, early diagnosis and immediate treatment with intravenous hydrocortisone are aspects to consider in similar cases. Analysis of the event through pharmacovigilance allowed it to be classified as severe, probably related to the enalapril consumption. This generates alerts to inform health staff and make decisions related to medications, which allow immediate action in order to reduce morbidity and mortality.